The Landscape: Italy and Russia: The general values for legislative and planning instrumentation - Maximova, Olga (International Planning History Society Proceedings, 2018)
The paper presents the results of the PhD research of author supported by the Erasmus Mundus Action 2 Programme of the European Union. The paper is dedicated to the landscape planning after European Landscape Convention, in particularly to the Italian experience, demonstrates the differences of understanding the landscape related to social, linguistic, economic, environmental aspects and its interrelationship. European Landscape Convention (Florence, 2000) defined that landscape has “an important public interest role in the cultural, ecological, environmental and social fields”. These intends various possibilities for new programs, for new tools, for new process and activity in regard the city as a landscape. The research investigates the theme of landscaping planning in Italy to answer the main question of the thesis: how can the ELC's addresses be applied to the Russian case through experience of Italian landscape planning. To achieve this goal, has been verified: the process of integrating the European Landscape Convention, the Italian legislative system and landscape planning tools.